Thermal Ablation of Lung Tumors: Focus on Microwave Ablation - Vogl, Thomas J.; Nour-Eldin, Nour-Eldin A.; Albrecht, Moritz Hans; Kaltenbach, Benjamin; Hohenforst-Schmidt, Wolfgang; Lin, Han; Panahi, Bita; Eichler, Kathrin; Gruber-Rouh, Tatjana; Roman, Andrei (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Background Image-guided thermal ablation can be used for the treatment of medically inoperable primary and metastatic lung cancer. These techniques are based on the heating up or freezing (cryoablation) of a volume of tissue around a percutaneous applicator that induces necrosis of the tumor.Method The English-language literature concerning thermal ablation of the lung was reviewed. Radiofrequency ablation (RFA) is the most widely performed and investigated of these techniques. Microwave ablation (MWA) represents a relatively new alternative that shares the same indications and is conducted in a very similar fashion as RFA. It has been experimentally and clinically shown that MWA produces larger, more spherical ablation zones over shorter periods of time compared to RFA. Seven different MWA systems are available in Europe and the USA with significant differences in the size and shape of the produced ablation zones.Results The types of complications caused by MWA and their rates of occurrence are very similar to those caused by RFA. The local progression rates after MWA of lung malignancies vary between 0 % and 34 % and are similar to those in the RFA literature.Conclusion Despite technical improvements, the current generation of MWA systems has comparable clinical outcomes to those of RFA.Key Points Citation Format
Keywords: ablation procedures; lung; metastases; NSCLC